KAJIAN PEMBERIAN PUPUK FOSFAT DAN SAAT PEMBENAMAN AZOLLA TERHADAP PERTUMBUHAN DAN HASIL TANAM AN PADI SAWAH - Budi Sutoto, Supono (MAPETA, 2008)
The study aimed to know the time of Azol1a application and the dose of P fertilizer which gave the best rice yield. The experiment was done from November 2005 to March 2006, in the field and green house of Agricultural Faculty UPN "Veteran" Yogyakarta, Condong Catur, Yogyakarta. The pot experiment was arranged in Randomized Completely Design with two factor and three replication. The first factor was the timing ofAzofla application: no Azolla, 3,4,5 and 6 weeks after planting. The second factor was the dose of P fertilizer: 100 and 150 kg SP-36. The datas were analysed by analysis varian and Duncan Test 5%. The result showed that there was no interaction between the time of Azolla application and the dose of P fertilizer.The time of Azolla application 4 week after planting gave the best productive suckers , it was also for the dose P fertilizer 150kg/ha. Keywords: Azolla, P fertilizer and lowland rice